Development of the human capital of youth in the agrarian sphere - A. V. Zinich; O. S. Evdokhina; O. V. Kondratieva (Вестник СибАДИ)
The present article is devoted to research of problems of developing human capital in the agrarian sphere. The authors have characterized adaptation processes on the market of agrarian work, as a basis of successful process of increasing the human capital’s cost. There are determined the main problems influencing formation and development of labour resources of the region. The authors have contemplated the directions of improving social and labor relations within public-private partnership.